Simulation of Grid Connected Three-Level Neutral-Point-Clamped qZS Inverter using PSCAD - Roncero-Clemente, Carlos; Romero-Cadaval, Enrique; Husev, Oleksandr; Vinnikov, Dmitri; Stepenko, Serhii (Electrical, Control and Communication Engineering, 2013)
This paper is focused on a single-phase three-level neutral-point-clamped quasi-z-source inverter when it is operating being connected to the electrical grid. A control strategy for injecting current synchronized in phase with the voltage at the point of common coupling has been proposed and studied. It is achieved by means of controlling the output voltage between branches adjusting the output current by using a d-q frame and the analysis of the output filter. The control strategy generates the reference to be used in the modulation technique and it has been validated with and without shoot-through switching states. A method to calculate the minimum value of the shoot-through duty cycle is also explained in order to assure the proper control of the injected current when the input voltage is less than peak value of the grid voltage. It is an important feature because 3L-NPC qZSI due to its possibility of boosting input voltage in a single stage would operate better than a traditional inverter, for instance in photovoltaic applications when the value of irradiance is decreased. The presented results have been obtained using PSCAD/EMTDC as a simulation tool.